Key concepts in economic geography - Aoyama, Yuko (Key concepts in human geography, 2011)
Key Concepts in Economic Geography is a new kind of textbook that forms part of an innovative set of companion texts for the Human Geography sub-disciplines. Organized around 20 short essays, Key Concepts in Economic Geography provides a cutting edge introduction to the central concepts that define contemporary research in Economic Geography. Involving detailed and expansive discussions, the book includes: a) an introductory chapter providing a succinct overview of the recent developments in the field; b) over 20 key concept entries with comprehensive explanations, definitions and evolutions of the subject; c) extensive pedagogic features that enhance understanding including figures, diagrams and further reading. An ideal companion text for upper-level undergraduate and postgraduate students in economic geography, the book presents the key concepts in the discipline, demonstrating their historical roots and contemporary applications to fully understand the processes of economic change, regional growth and decline, globalization, and the changing locations of firms and industries. -- Back cover.